2006
DOI: 10.1002/ajp.20231
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective evaluation of the incidence and severity of hemosiderosis in a large captive lemur population

Abstract: Significant concern has been generated about the susceptibility of captive lemurs to iron storage disease, which has led some researchers to propose husbandry changes regarding dietary iron. In the current study we sought to determine the history, severity, and prevalence of iron storage disease within a large captive lemur population. Iron concentration and hemosiderin accumulation in a target organ, the liver, were assessed in necropsy specimens from 15 different species (n=153) of lemurs over a 12-yr period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 26 publications
2
19
1
1
Order By: Relevance
“…Increased hepatic iron concentration has been demonstrated in several lemurs, common marmosets (Callithrix jacchus) and other New World monkeys (Callithrix, Cebuella, Lagotrix, Saimiri and Sanquinus) (Gonzales et al, 1984;Gottdenker et al, 1998;Lowenstine and Munson, 1999;Williams et al, 2006). It is also a common finding in captive lowland gorillas (Gorilla gorilla graueri) and free-ranging mountain gorillas (Lowenstine and Munson, 1999).…”
Section: Iron Storage In Hon-human Primatesmentioning
confidence: 88%
See 3 more Smart Citations
“…Increased hepatic iron concentration has been demonstrated in several lemurs, common marmosets (Callithrix jacchus) and other New World monkeys (Callithrix, Cebuella, Lagotrix, Saimiri and Sanquinus) (Gonzales et al, 1984;Gottdenker et al, 1998;Lowenstine and Munson, 1999;Williams et al, 2006). It is also a common finding in captive lowland gorillas (Gorilla gorilla graueri) and free-ranging mountain gorillas (Lowenstine and Munson, 1999).…”
Section: Iron Storage In Hon-human Primatesmentioning
confidence: 88%
“…Captive lemurs have been found to be particularly prone to iron storage, mostly in the liver, spleen, lymph nodes and duodenum. Approximately 32e100% of the lemur population can be affected, of which up to 50% may have finally died as a direct result of excessive iron load (Gonzales et al, 1984;Spelman et al, 1989;Glenn et al, 2006). Similarly, in a study of iron metabolism in free-ranging ring-tailed lemurs (Lemur catta), iron concentrations, ferritin and transferrin saturations were lower when compared with captive individuals (Dutton et al, 2003).…”
Section: Iron Storage In Hon-human Primatesmentioning
confidence: 91%
See 2 more Smart Citations
“…A retrospective analysis of a captive lemur population (n ¼ 153) encompassing 15 different species displayed a 32% prevalence of hemosiderosis. 18 Previous studies had reported a prevalence of hemosiderosis in lemurs as high as 69% to 100%. 5,19,30 Hepatic hemosiderosis is also very common in captive callitrichids, with postmortem studies revealing a 94.4% prevalence among callitrichids from the Bronx Zoo.…”
Section: Introductionmentioning
confidence: 99%